Aspergillus Thyroiditis: A Complication of Respiratory Tract Infection in an Immunocompromised Patient. (18th December 2013) - Alvi, Madiha M.; Meyer, David S.; Hardin, Nicholas J.; deKay, James G.; Marney, Annis M.; Gilbert, Matthew P.
Abstract : A 59-year-old male with past medical history significant for non-Hodgkin's lymphoma status after chemotherapy presented with acute onset of neck pain, odynophagia, and dysphagia associated with subjective fever, chills, and dyspnea. Physical findings included a temperature of 38.4°C, hypertension, and tachycardia. Patient was found to have anterior neck tenderness. Laboratory evaluation revealed neutropenia. The patient was started on empiric antibacterial and antiviral therapy and continued on home prophylactic antifungal treatment. Thyroid function tests revealed overt hyperthyroidism. A thyroid ultrasound showed heterogeneous echotexture without discrete nodules. Subacute thyroiditis was treated with methylprednisolone, metoprolol, and opiate analgesics. Patient's antibacterial, antifungal, and antiviral treatments were broadened. A fine needle aspiration was not conducted. The patient's condition deteriorated rapidly over his brief hospital course and he expired. Autopsy showed fungal thyroiditis secondary to disseminated invasive Aspergillus . This report describes the presentation of fungal thyroiditis secondary to disseminated invasive Aspergillus originating from the respiratory tract. The authors review the diagnostic challenges, pathophysiology, and treatment of this condition.